How much is your health worth? A research agenda on valuation processes and markets for medicines - Etienne Nouguez (economic sociology_the european electronic newsletter, 2020)
The stakes around the global and national medicines markets have been rising steadily for the last twenty years. From the controversies over patents surrounding HIV treatments and the right of developing countries to infringe these patents and develop generic copies in the late 1990s ('t Hoen 2002; Coriat 2008), to the current debates over the exorbitant prices of certain medicines and the sustainability of the expenditure they generate for national health insurance (Vogler et al. 2016), or, in the current context of the Covid-19 pandemic, over supply disruptions and struggles between countries to access treatments, tests, and protective masks - medicines and health products raise a series of fundamental questions.
Keywords: 300